HABITER L’ENFANCE APPROCHE DE L’HABITAT DANS LES PREMIERS RECITS D’EUGENE SAVITZKAYA - Domingues de Almeida, José (2019)
The author undertakes the approach of the specific importance of the relation with inhabited or uninhabited spaces in the imaginary and narrative framework of fictional texts by the contemporary francophone Belgian writer, Eugène Savitzkaya from Mentir (1977) to En vie (1994). He emphasises the relevance of habitat as a basis of child imagination and daily life poetization. In fact, space seems to be much more like a symbolic and poetic reference in Savitzkaya’s work and it enables him to express himself and his own childhood in a self-fictional way.